Analysis Of Financial Statements Of Company Operating Segments In Accordance With PSAK 108 At PT Mayora Indah Tbk And Its Subsidiaries - Nur Miftahul Janah; Mutiara Rahmanisa; Ulfa Wati; Emanuel Bria; Rimi Gusliana Mais (International Journal of Multidisciplinary Research and Innovation, 2025)
This study aims to analyze the application of Financial Accounting Standards (PSAK) No. 108 regarding the reporting of operating segments at PT Mayora Indah Tbk and its subsidiaries for the period 2023–2024. The research method used is descriptive qualitative, with data analysis techniques that include a 10% test on segment revenue, profit/loss, and assets. The results of this test show that two main segments packaged processed foods and packaged processed beverages meet the 10% threshold and are therefore required to be reported as operating segments. Conversely, the financial services segment did not meet the reporting criteria due to its contribution being below the materiality threshold set in PSAK 108. These findings suggest that the implementation of PSAK 108 at PT Mayora Indah Tbk is generally good but not fully effective, particularly in terms of the disclosure of insignificant segments. Although the company has largely adhered to segment reporting requirements, it still faces challenges in providing full transparency regarding smaller segments that do not have a significant impact on overall financial performance. This study is expected to serve as a useful reference for companies and stakeholders in Indonesia, guiding them to improve compliance with segment financial reporting standards. Additionally, the research highlights the importance of accurately applying materiality thresholds and ensuring that segment disclosures align with actual business activities. By improving segment reporting practices, companies can achieve more transparent and accountable financial reporting, which will ultimately enhance the decision-making process for stakeholders and foster greater trust in the company’s financial management.